Update: A year ago, but the first answer is not clear with me. I bounty this question again.

My question: I am looking for a proof or counterexample to the following inequality:

If $n \in \mathbb{N}$, and $a_1 \ge a_2 \ge \cdots \ge a_n \ge 0$ and $\alpha_1 \ge \alpha_2 \ge \cdots \ge \alpha_n \ge 0$ then

$${\left(\sum_{i=1}^{n}{a_i^{\alpha_i}} \right)}^n \ge \prod_{i=1}^{n}{\left(\sum_{j=1}^{n}{a_i^{\alpha_j}} \right)}$$

If $n \in \mathbb{N}$ and $a_1 \ge a_2 \ge \cdots \ge a_n \ge 0$ and $0 \le \alpha_1 \le \alpha_2 \le \cdots \le \alpha_n$ then

$${\left(\sum_{i=1}^{n}{a_i^{\alpha_i}} \right)}^n \le \prod_{i=1}^{n}{\left(\sum_{j=1}^{n}{a_i^{\alpha_j}} \right)}$$

Moreover equality holds in either case if and only if $a_1=a_2=a_3=...=a_n$.

[The original question claimed a proof when $n=2$ or $n=3$.]

  • $\begingroup$ I edited your question to make it a bit clearer. At the end you restated the inequalities for $n=2$ and $n=3$, but I didn't see a proof. So I deleted the $n=3$ case and added the details for $n=2$. $\endgroup$ – Mark Wildon Jun 19 '19 at 9:45
  • 1
    $\begingroup$ I think, the difference for $n=2$ is not $a_1^{\alpha_1}a_2^{\alpha_2} - a_1^{\alpha_2}a_2^{\alpha_1}$. $\endgroup$ – Fedor Petrov Jun 19 '19 at 10:48

The first inequality is not true for $n=2$, for example as =

0.0912    0.2256

alphas =

0.8281    1.7010





found by the following Matlab/Octave program:


for iter=1:1e4 as=cumsum(rand(1,n)); alphas=cumsum(rand(1,n));

LHS=sum(as.^alphas)^n; RHS=prod(sum(as.^(alphas')));

if LHS

as alphas LHS RHS




Let $a_1 \geq a_2 \geq \ldots a_n \geq 1$ and $r_1 \geq r_2 \geq \ldots r_n \geq 0$.

Then over all permutations $\pi$ of the $r_j$, the sum $\sum_{i=1}^{n}a_i^{r_{\pi_i}}$ is maximized when $r_i$ are in the same order as the $a_i$. The proof is similar to any standard proof of the original re-arrangment inequality.

For contradiction, suppose that some other permutation is larger. Then there exist terms $a^b$ and $c^d$ in the sum such that $a \geq c$ and $b \leq d$. But we have $a^d+c^b \geq a^b+c^d$, i.e. swapping these two exponents does not decrease the value of the sum.

To prove the inequality, re-write as $(a/c)^b \geq \dfrac{c^{d-b}-1}{a^{d-b}-1}$ and notice that the LHS is at least 1 and the RHS is at most 1.

Note: You need a weaker result and it may be sufficient to assume all the $a_i$s non-negative.

  • 1
    $\begingroup$ I don't think so. Do You prove that $a^d+c^b \ge a^c+a^b$ ? $\endgroup$ – Đào Thanh Oai Jul 20 '18 at 11:09
  • $\begingroup$ The answer above would be correct if each factor on the right-hand side was of the form $\sum_{j=1}^n a_{\sigma(j)}^{\alpha_j}$ for some permutation $\sigma$. But in fact $a_i$ is constant within each factor. $\endgroup$ – Mark Wildon Jun 19 '19 at 9:20

For the first inequality, it follows (when $a_n\geqslant 1$) from Aravind's claim that $\sum_i a_i^{\alpha_i}$ is not less than arithmetic mean of $b_1,\ldots,b_n$, where $b_i=\sum_j a_i^{\alpha_j}$. Thus not less than geometric mean too.

The second inequality looks false by trivial reasons: if $a_n=0$ and all $\alpha_i$'s are positive, RHS equals 0 while LHS not necessary.

  • $\begingroup$ is the first inequality true if we let $a_n \ge 1$ ? $\endgroup$ – Đào Thanh Oai Jun 19 '19 at 11:19
  • $\begingroup$ Yes, I had to mention this. $\endgroup$ – Fedor Petrov Jun 19 '19 at 11:42

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.